Extracellular micro/nanovesicles rescue kidney from ischemia‐reperfusion injury. Issue 8 (4th January 2019) - Farzamfar, Saeed; Hasanpour, Akram; Nazeri, Niloufar; Razavi, Hengameh; Salehi, Majid; Shafei, Shilan; Nooshabadi, Vajiheh T.; Vaez, Ahmad; Ehterami, Arian; Sahrapeyma, Hamed; Ai, Jafar
Abstract: Acute renal failure (ARF) is a clinical challenge that is highly resistant to treatment, and its high rate of mortality is alarming. Ischemia–reperfusion injury (IRI) is the most common cause of ARF. Especially IRI is implicated in kidney transplantation and can determine graft survival. Although the exact pathophysiology of renal IRI is unknown, the role of inflammatory responses has been elucidated. Because mesenchymal stromal cells (MSCs) have strong immunomodulatory properties, they are under extensive investigation as a therapeutic modality for renal IRI. Extracellular vesicles (EVs) play an integral role in cell‐to‐cell communication. Because the regenerative potential of the MSCs can be recapitulated by their EVs, the therapeutic appeal of MSC‐derived EVs has dramatically increased in the past decade. Higher safety profile and ease of preservation without losing function are other advantages of EVs compared with their producing cells. In the current review, the preliminary results and potential of MSC‐derived EVs to alleviate kidney IRI are summarized. We might be heading toward a cell‐free approach to treat renal IRI. Abstract : This review provides an overview of the current knowledge related to the potential use of extracellular vesicles (EVs) in protecting kidney from ischemia–reperfusion injury and discuss the promising future of EVs as an alternative to conventional cell therapy approaches.